Medroxyprogesterone acetate induces C6 glioma chemosensitization via antidepressant-like lysosomal phospholipidosis/myelinosis in vitro - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2007)
The authors have previously shown that medroxyprogesterone acetate (MPA) inhibits growth and increases drug sensitivity in C6 glioma with myeloid bodies. Myeloid bodies can occur in cells either due to robust toxicity with mitochondrial membrane disruption or due to milder events such as seen in lysosomal-phospholipidosis. Exact patterns of myelinosis accompanying to MPA chemo-sensitization is important, because uncoupling of nuclear versus mitochondrial toxicity of anti-neoplastics by MPA would lead to safer employment of glioma chemotherapy with reduced neurotoxicity. By monitoring and comparing cell kinetics with fine structural features of cell death, the authors estimated subcellular effects accompanying growth-inhibitory drug actions in C6 glioma. The analysis revealed that MPA induced mainly lysosomal phospholipidosis, while inhibiting clonogenicity alone and augmenting procarbazine efficacy. It induced apoptosis in combination with cisplatin. It reduced mitochondrial-damage-based early cytotoxicity of methotrexate, yet it did not hinder its anti-clonogenic efficacy. Progesterone analogues-similar to antidepressants-inhibit cholesterol esterification, and this efficacy relates with their P-glycoprotein inhibition. Reducing esterification and plasma-membrane localization of cholesterol may lead MPA induction of lysosomal phospholipidosis, growth indolency, and drug sensitization in glioma.
Keywords: chemotherapy; glioma; medroxyprogesterone; INTRATHECAL METHOTREXATE; CELL-LINE; CISPLATIN; CYTOTOXICITY; MITOCHONDRIA; INHIBITION; APOPTOSIS; TOXICITY; NECROSIS; TUMORS